Phospholipase D activity couples plasma membrane endocytosis with retromer dependent recycling. - Thakur, R.; Panda, A.; Coessens, E.; Raj, N.; Yadav, S.; Balakrishnan, S.; Zhang, Q.; Georgiev, P.; Basak, B.; Pasricha, R.; Wakelam, M.J.; Ktistakis, N.T.; et al. (eLife, 2016)
During illumination, the light-sensitive plasma membrane (rhabdomere) of Drosophila photoreceptors undergoes turnover with consequent changes in size and composition. However, the mechanism by which illumination is coupled to rhabdomere turnover remains unclear. We find that photoreceptors contain a light-dependent phospholipase D (PLD) activity. During illumination, loss of PLD resulted in an enhanced reduction in rhabdomere size, accumulation of Rab7 positive, rhodopsin1-containing vesicles (RLVs) in the cell body and reduced rhodopsin protein. These phenotypes were associated with reduced levels of phosphatidic acid, the product of PLD activity and were rescued by reconstitution with catalytically active PLD. In wild-type photoreceptors, during illumination, enhanced PLD activity was sufficient to clear RLVs from the cell body by a process dependent on Arf1-GTP levels and retromer complex function. Thus, during illumination, PLD activity couples endocytosis of RLVs with their recycling to the plasma membrane thus maintaining plasma membrane size and composition.